Programa de Capacitación Basado en el Modelo de kirkpatrick para Mejorar el Nivel de Seguridad en Operaciones con Montacargas en la Empresa Executive Solutions s.a. – Operación Lindley - Avalos Rodriguez, Amir Carlos (2017)
This thesis demonstrates that the implementation of a training program developed under the model of Kirkpatrick improved the level of security of the company Executive Solutions S.A.C. in its operation at the Lindley - Trujillo plant. Executive Solutions S.A.C. Had a talk program which only had the purpose of complying with law 29783, but were not aimed at increasing the culture of safety in their operations with forklifts or indicators. The implementation of the "Zero Accident" training program developed under Kirkpatrick's training and evaluation model and using tools for adult learning achieved a 74.4% satisfaction level, improving staff work climate. In addition, the level of knowledge increased from 68.5% to 81.9%, demonstrating the effectiveness of the training program in the transfer of knowledge. The goal of 80% of the indicator of safe behavior was also achieved, since it increased from 76.03% to 81.03%. The study shows that these increases in the indicators are significant according to statistical tests of Shapiro Wilk and Wilcoxon.